PENGGUNAAN MODEL PEMBELAJARAN WORD SQUARE UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA MATA PELAJARAN IPS KELAS IV SEKOLAH DASAR NEGERI 005 SEDINGINAN KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Marzuki, Muhammad; ', Gusnardi; ', RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: Given the importance of foster or create interaction in learning ,application of learning strategies in an attempt to create such interactions , because thechosen strategy influential teacher in learning. Selection of strategy in learning mustpay attention to the conditions , needs and abilities of students . In connection with theschool as a venue for the educational process is expected to be able to equip thestudents to have the ability mendimensi cognitive , effective and psychomotor inharmony , so that produce human resources that are reliable and responsible for theprogress of society and the nation in addition to competing with the nation other. Afterresearchers made observations and experiences in the fourth grade primary school 005Sedinginan subdistrict Tanah Putih district Rokan Hilir.Keywords : Model Word squre and Student Motivation